Effect of shoot removal on bud fruitfulness and yield of Vitis vinifera cv. ‘Crimson Seedless’ in the Western Cape - Taylor, Nicolette Jane (University of Pretoria, 2015)
Dissertation (MInst Agrar)--University of Pretoria, 2014.